MENGUNGKAP MAKNA LAFADZ AL-MAGHDU DAN AD-DHOLLIN DALAM SURAT AL-FATIHAH : Studi Komparatif Penafsiran Muhammad Asad dan Al-Qurthubi - Muhammad Yahya; Asep Ahmad Fathurrahman; Ade Jamarudin (TAFAKKUR : Jurnal Ilmu Al-Qur'an dan Tafsir, 2023)
This article aims to discuss two different interpretations in the last verse in surah al-Fatihah, to be precise in the pronunciation of Al-Maghdu and Ad-Dhollin. This research uses a qualitative method, by using a literature study approach. The research in this article guides the reader in comparing two different interpretations. Among the discussions are the profiles of the two interpreters and the comparison of their exegesis. The conclusion shows that the meaning of lafadz Al-Maghdu and Ad-Dhollin from Muhammad Asad’s view is to mankind in general and specifically to non-Muslims. In contrast, the interpretation of Al-Qurthubi is to Muslims, where Al-Maghdu were people who were heretical and Ad-Dhollin were people who did not follow the sunnah of the Prophet.